Production Of Prodigiosin By Serratia Marcescens Ibrl Usm84 For Lipstick Formulation - Nazari, Teh Faridah (2018)
Microorganisms provide plenty of natural pigments as a safe alternative to the synthetic dyes in many industrial applications including cosmetics, food, textile, pharmaceutical and aquaculture industries. This research was aimed to study the natural red pigment prodigiosin with antimicrobial activity of a marine bacterium. The finding of natural colorant with antimicrobial activity can give benefits to many industries and acts as a natural coloring agent with preservative value simultaneously to the industrial products. In this study, Serratia marcescens IBRL USM84 was isolated from a local marine sponge Xetospongia testudinaria from Pulau Bidong, Terengganu. The analysis of antimicrobial activity from intracellular and extracellular pigments was performed and found that the antimicrobial activity from intracellular pigment was greater. The analysis of pigment production revealed that intracellularly and extracellularly extracted pigments were able to produce different color intensity at different quantity, where the pigment from intracellular yielded 7.02 g/L compared to extracellular pigment that was 0.25 g/L only. From the enhancement process, S. marcescens IBRL USM84 produced higher prodigiosin pigment and better antibacterial activity after 48 hours of cultivation period with medium initial pH at 7, incubated at 25oC and with 150 rpm of agitation speed, the addition with 0.2 % of agar and 1% of maltose under light condition. The dichloromethane extract from intracellular pigment produced by S. marcescens IBRL USM84 showed higher pigmentation strength with greater antimicrobial activity compared to other extracts.